Speak easy : dazzle every audience and leave them begging for more - Gibbons, Barry J. (New York : Perigee, 2007)
An introduction to public speaking shares a series of practical guidelines on how to produce effective and interesting oral presentations, from creating the perfect wedding toast to mastering audiovisual equipment.
Includes index.
Originally published in Great Britain in 2005 by the Infinite Ideas Co.
Keywords: Public speaking